Logistics Challenges in the Automotive Industry 2020–2023 - Molnár, László; Tégla, Zsolt (Acta Carolus Robertus, 2023)
From 2020 onwards, the automotive industry will face serious challenges. Covid-19 has significantly changed the way supply chains operate, making previously predictable purchasing and distribution systems completely unpredictable. Logistics processes had to be redesigned. Logistics methods that had worked well in the past - JIT, JIS, ABC-analysis based sourcing strategies - that were industry standard and helped Lean manufacturing to reduce inventory levels and deliver on time, have become ineffective or have been transformed by the changed economic environment. These factors have led to significant changes in logistics processes, as the ever-changing economic environment, hectic energy costs and significant wage increases have required accurate and up-to-date measurement and control of planning and operational processes, in addition to the strategic level. In addition to economic performance, survival characteristics such as flexibility, adaptability, modularity or the ability to connect and integrate with larger systems have emerged in automotive businesses. All these features are now essential for the smooth running of automotive processes. Logistics rules that were previously in place have had to be rethought by companies and Küehne+Nagel Ltd as a logistics provider has had to make different strategic choices, learning from the economic volatility of the last 3 years. 2023 has brought new long-term challenges for automotive suppliers and logistics providers, as the preparation and transition to electric automotive processes has brought with it the emergence of completely different component and inventory systems and suppliers.
Keywords: scarcity of raw materials; flaxibility; modularity; logistical reengineering; electric car manufacturing